Development and Implementation of an Inpatient Otolaryngology Consultation Service at an Academic Medical Center. Issue 2 (February 2018) - Huddle, Matthew G.; London, Nyall R.; Stewart, C. Matthew
Abstract : Objectives: To design and implement a formal otolaryngology inpatient consultation service that improves satisfaction of consulting services, increases educational opportunities, improves the quality of patient care, and ensures sustainability after implementation. Methods: This was a retrospective cohort study in a large academic medical center encompassing all inpatient otolaryngology service consultations from July 2005 to June 2014. Staged interventions included adding fellow coverage (July 2007 onward), intermittent hospitalist coverage (July 2010 onward), and a physician assistant (October 2011 onward). Billing data were collected for incidences of new patient and subsequent consultation charges. The 2-year preimplementation period (July 2005–June 2007) was compared with the postimplementation periods, divided into 2-year blocks (July 2007–June 2013). Outcome measures of patient encounters and work relative value units were compared between pre- and postimplementation blocks. Results: Total encounters increased from 321 preimplementation to 1211, 1347, and 1073 in postimplementation groups ( P < 0.001). Total work relative value units increased from 515 preimplementation to 2090, 1934, and 1273 in postimplementation groups ( P < 0.001). Conclusions: A formal inpatient consultation service was designed with supervisory oversight by non–Accreditation Council for Graduate Medical Education fellows and then expanded to include intermittent hospitalist management, followed by the addition of a dedicated physician assistant. These additions have led to the formation of a sustainable consultation service that supports the mission of high-quality care and service to consulting teams. Abstract : Obtaining timely and high-quality surgical subspecialty consultations in hospital inpatients and emergency departments can present a challenge in all hospital settings. This study aimed to create a sustainable otolaryngology consultation service to meet the goals of improved satisfaction of the consulting services, increased educational opportunities for residents, and improved quality of patient care.